Olive mill wastes — A growing medium component for seedling and crop production of lettuce and chicory - Kelepesi, Sofia; Tzortzakis, Nikos G. (My University, 2009)
Olive mill waste management has been a major issue of environmental concern for all olive oil-producing countries. Several soil amendments have been used to improve the physical and chemical characteristics of rootzone profiles and mixes. Olive mill waste (OW, olive stone and pulp) in different ratios (10%, 30%, or 50% v/v) was investigated for use in production of lettuce (Lactuca sativa L., cvs. Paris Island and Corsica) and chicory (Cichorium intybus L., cv. Chicory white stem) seedlings by replacing part of the peat or perlite in the growing medium. Also evaluated was use of OW (10% or 30% v/v) in soil for production of lettuce (cv. Paris Island). The OW extracts at 10-1 to 10-6 accelerated seedling germination and radicle length. Under nursery conditions, the addition of OW as substrate component improved seed emergence for chicory and lettuce (cv. Corsica) but suppressed lettuce cv. Paris Island seed emergence but not mean emergence time. Olive mill waste combined with perlite in different ratios performed better regarding seed emergence compared with mixtures of OW and peat. Addition of OW in perlite and/or peat reduced leaf fresh weight and leaf numbers. Plant height decreased only in substrates where perlite was mixed with OW. Under greenhouse conditions, increased OW content in soil reduced (up to 25%) lettuce plant fresh weight compared to the control. This effect was mainly due to shorter leaves rather the number of leaves produced. Reduced plant growth occurred with reduced root fresh weight; root length was not affected by treatment. Use of soil:OW at 90:10 v/v mix can be applied to lettuce in the greenhouse; diluted OW extract and OW (at 10%-30%) may be used for seed priming and seedling production, respectively, and may increase profit.
Keywords: Chicory; Cichorium intybus; Lactuca sativa; Lettuce; Mill waste; Olea europaea; Olive; Peat; Perlite; Plant growth; Seed emergence